2021
DOI: 10.3889/oamjms.2021.5974
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sleep Disorders in Adolescents and its Relation with Screen Time during the COVID-19 Pandemic Era

Abstract: BACKGROUND: Sleep disorders encompass disturbances in the amount, quality, or timing of sleep. Several factors have contributed to sleep disorders in adolescents, including the use of electronic devices. In the COVID-19 pandemic era, there is a rising trend of screen time. AIM: The objective of the study was to identify the prevalence of sleep disorders in adolescents and its relation with screen time during the COVID-19 pandemic era. METHODS: This is a cross-sectional study involving students aged 15–18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 19 publications
(25 reference statements)
0
13
1
3
Order By: Relevance
“…The Pittsburgh Sleep Quality Index (PSQI) scale was used in five studies and was the most commonly used scale in adolescents. Three studies found that sleep quality worsened during the COVID‐19 pandemic (Silva et al, 2022 ; Windiani et al, 2021 ; Zhou et al, 2020 ). Two studies pointed to an increased prevalence of sleep disturbances (Windiani et al, 2021 ; Zhou et al, 2020 ), and four studies showed an increase in sleep duration during COVID‐19 in adolescents (Genta et al, 2021 ; Silva et al, 2022 ; Windiani et al, 2021 ; Zhou et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pittsburgh Sleep Quality Index (PSQI) scale was used in five studies and was the most commonly used scale in adolescents. Three studies found that sleep quality worsened during the COVID‐19 pandemic (Silva et al, 2022 ; Windiani et al, 2021 ; Zhou et al, 2020 ). Two studies pointed to an increased prevalence of sleep disturbances (Windiani et al, 2021 ; Zhou et al, 2020 ), and four studies showed an increase in sleep duration during COVID‐19 in adolescents (Genta et al, 2021 ; Silva et al, 2022 ; Windiani et al, 2021 ; Zhou et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the use of electronic devices, eight studies reported an increase during the pandemic with an association with sleep (Abid et al, 2021 ; Aguilar‐Farias et al, 2021 ; Dutta et al, 2022 ; Liu et al, 2021 ; Ranjbar et al, 2021 ; Silva et al, 2020 ; Windiani et al, 2021 ). An increase of 3.05 h of electronic use was observed during COVID‐19; before the pandemic the average time was 1.66 h. Another study found that the increase was 36% in children.…”
Section: Resultsmentioning
confidence: 99%
“…90 Non-academic screen time was negatively associated with sleep duration (r=À0¢41; p=<0¢01). 92 Overall screen time was also associated with increased odds of sleep disorders (OR=3¢80 95%CI 1¢09 −13¢1), 107 and tablet (r = 0¢17; p=<0¢05) and smartphone time (r = 0¢30; p=<0¢001) were both associated with 'sleep problems' (TV time was not significantly associated with sleep problems). 91 Problematic screen time behaviours.…”
Section: Mentalmentioning
confidence: 99%
“…57 Children. In children, 24 studies 9,11,15,66,72,74,76,79,81,83,86,88,[90][91][92]95,98,99,103,[105][106][107]109,111 reported 181 outcomes across the following areas: diet, eye health, mental health, physical activity, parental health, physiology, sleep, and problematic behaviours (see Supplementary Table 3).…”
Section: Associations Between Screen Time and Multiple Correlatesmentioning
confidence: 99%
See 1 more Smart Citation